Analisis Strategi Bersaing PT. Bank Rakyat Indonesia Cabang Klaten - , Ali Pati Agung ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to evaluate the internal and external factors of PT. BRI Klaten Branch that influence the application of its competitive strategy and formulate the appropriate competing strategy for the company to win the competition in the banking industry. This study utilizes several data analysis method including: general environment analysis, industry environment analysis using Five Forces model and Key Success Factors, and internal environment analysis using Value Chain, SWOT analysis and competitive strategy analysis. These analysis methods are intended for the company to outperform the competition and formulate the appropriate company competitive strategy. The results of the analysis will also assist the company in reviewing the previous and current decisions of the competitors. The result of the research shows that the strategy used by Bank BRI Klaten Branch is Best Cost Provider, a strategy that combines low cost with product differentiation with a purpose of obtaining the best cost structure with high quality. This strategy is also in line with the companyâs vision and mission that is to be a well-known commercial bank that always put forward customerâs satisfaction.